Kazakhstan’s universities: global challenges and local duties improving education quality - Nurgaliyeva, Saniya; Zeinolla, Saule; Aben, Assel; Iskendirova, Saule; Ismukhanova, Gulnara (International Journal of Evaluation and Research in Education (IJERE), 2025)
Over the years of independence, Kazakhstan has developed a higher education (HE) system that incorporates both national characteristics and international standards. However, the system still struggles to meet new challenges, and its scale, while comparable to global standards, does not yet reflect the growing requirements for quality education essential for ensuring competitiveness. The study aims to evaluate the extent of variability in Kazakhstan’s policies as they navigate between global challenges and local objectives in the pursuit of higher education quality. A quantitative method was utilized to collect and analyze the study data to identify relationships, test hypotheses, and draw generalizations. The study sample consists of a total of 1,200 educators from various universities. The study findings revealed that Kazakhstan is rapidly advancing to the third stage of HE internationalization, striking a balance between importing and aspiring to export HE. This study is important as it provides valuable insights into how Kazakhstan’s modern universities can effectively manage the intersection of global challenges and regional obligations to enhance the quality of HE.